Questioning Nature in Late Middle Ages. A History of Method, Praxis and Innovation - Giovanni Patriarca (Medievalia)
This essay traces the interconnections between method, praxis and innovation with their epistemological consequences at the end of the Middle Ages. In the wake of scholastic natural philosophy, this vibrant process marks a milestone in the history of science. During the Thirteenth and Fourteenth centuries a profound transformation takes place in the way of observing nature through a meticulous data collection, experiments and subsequent analysis. In this cultural framework, the Franciscans analyze the realities of the world with an extremely original pragmatic dynamism. This approach gives priority to a practical sense of thinking through a transformative action which opens the doors to a pioneering scientific method and contributes to a long series of innovations. A positive result is an advanced didactics—especially developed by Buridan, Oresme and their followers —that will have a great impact on a continental level, changing the common ground of European science.